Identifying impediments to long‐distance mammal migrations. Issue 1 (26th August 2014) - Seidler, Renee G.; Long, Ryan A.; Berger, Joel; Bergen, Scott; Beckmann, Jon P.
Abstract In much of the world, the persistence of long‐distance migrations by mammals is threatened by development. Even where human population density is relatively low, there are roads, fencing, and energy development that present barriers to animal movement. If we are to conserve species that rely on long‐distance migration, then it is critical that we identify existing migration impediments. To delineate stopover sites associated with anthropogenic development, we applied Brownian bridge movement models to high‐frequency locations of pronghorn (Antilocapra americana) in the Greater Yellowstone Ecosystem. We then used resource utilization functions to assess the threats to long‐distance migration of pronghorn that were due to fences and highways. Migrating pronghorn avoided dense developments of natural gas fields. Highways with relatively high volumes of traffic and woven‐wire sheep fence acted as complete barriers. At crossings with known migration bottlenecks, use of high‑quality forage and shrub habitat by pronghorn as they approached the highway was lower than expected based on availability of those resources. In contrast, pronghorn consistently utilized high‑quality forage close to the highway at crossings with no known migration bottlenecks. Our findings demonstrate the importance of minimizing development in migration corridors in the future and of mitigating existing pressure on migratory animals by removing barriers, reducing the development footprint, or installing crossing structures. Identificación de los Impedimentos para las Migraciones de Larga Distancia de Mamíferos